AN ANALYSIS ON K-POP FANDOM SLANG WORD-FORMATION IN THE DRAMA ‘HER PRIVATE LIFE’ - Megarani, Shandina; Dini, Jelita (UI Scholars Hub, 2021)
Slang is a language that is used daily and continues to grow due to the development of social media among fan communities. Each fan community has used slang specific to their interests, one of them being the K-Pop fandom. Despite the international growth of the K-Pop fandom and the spread of its cultural influence over recent years, there has been a lack of discussion on the linguistic aspect of its community, on the slang generated and used by its fan community in particular. Therefore, this research aims to expound on how K-Pop fandom slang words found in the drama ‘Her Private Life’ are formed. The study based its theoretical framework on the National Institute of Korean Language’s (2014) classification of new words in Korean based on its word-formation process. Out of the 24 slang words analyzed from the drama ‘Her Private Life’, there are 3 slang words in the form of a single word and 21 slang words in the form of a complex word. In the case of single-word form slang words, all 3 are created through the borrowing process; while complex-word form slang words are mostly created through the blending process, equating to 9 words in total.